2018
DOI: 10.1007/s10943-018-0562-x
|View full text |Cite
|
Sign up to set email alerts
|

“What Goes Around Comes Around”: Attitudes and Practices Regarding Ageing and Care for the Elderly Among Moroccan Muslim Women Living in Antwerp (Belgium)

Abstract: The aim of this article is threefold. First, we seek to elicit the attitudes and practices of middle-aged and elderly Moroccan Muslim women towards ageing and care for the elderly. Second, we aim to identify possible differences between middle-aged and elderly women's attitudes and practices. Third, we seek to explore which role religion plays in their attitudes and practices. Qualitative empirical research was conducted with a sample of middle-aged and elderly Moroccan Muslim women living in Antwerp (Belgium)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Thus, while demographic, epistemological, and socio-economic trends as well as globalisation may be impacting the efficacy of informal caregiving, in South African Muslim families, a strong preference remains for the care of PWD at home. This outcome is similar to related research that considers the role of Confucian filial piety values in caregiving for the elderly [6,7].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, while demographic, epistemological, and socio-economic trends as well as globalisation may be impacting the efficacy of informal caregiving, in South African Muslim families, a strong preference remains for the care of PWD at home. This outcome is similar to related research that considers the role of Confucian filial piety values in caregiving for the elderly [6,7].…”
Section: Discussionsupporting
confidence: 86%
“…Vazifeh doust et al ( 2020 ) demonstrated how Islamic-based treatments in hospital settings were effective in helping children with cancer to adapt to treatment. Ahaddour et al ( 2020 ) showed how Islamic beliefs integrated into aged care facilities in Belgium provided older Muslim residents with a sense of dignity. These examples provide a seamless illustration depicting the harmony of personal and organizational health literacy, through respecting that Islamic beliefs are essential to a Muslim’s way of life, in childhood, throughout life and in death.…”
Section: Discussionmentioning
confidence: 99%
“…We found instances in which religion was used as a reason to reject the concept of social position altogether. This line of reasoning was based in the idea that comparing oneself to others is morally rejectable according to the principles of religion (Ahaddour, van den Branden & Broeckaert, 2018;Buitelaar, 2006). In these cases, individuals based their social position on being a good person (or Muslim) instead.…”
Section: Discussionmentioning
confidence: 99%